The effect of Ag@SiO2 core‐shell nanoparticles on the dielectric properties of PVDF based nanocomposites. Issue 6 (3rd February 2020) - Weng, Ling; Wang, Xiaoming; Zhang, Xiaorui; Guan, Lizhu; Liu, Lizhu; Zhang, Hexin; Cui, Weiwei
Abstract: High dielectric properties material has a profound influence on the development of electronic power system, polymer based composites obtained a great number of achievements on it. A new strategy, which covered a layer of insulation on the surface of the inorganic particles to form a core‐shell structure, then used it for composites is a good choice. In this article, a series of PVDF based nanocomposite with different contents were prepared by using PVDF flexible polymer as substrate and core‐shell structure Ag@SiO2 nanoparticles as fillers. The effects of Ag@SiO2 core‐shell nanoparticles on the structure and properties of composites were investigated. Results showed that Ag@SiO2 has a typical core‐shell structure and the diameter size of Ag@SiO2 nanoparticles is 100 nm in average with about 20 nm thickness of SiO2 shell. XRD analysis showed that the addition of Ag@SiO2 nanoparticles induce a transition on crystal structure of PVDF from multiphase to mainly β phase, which result in an improvement on ferroelectric properties of composites. Broadband dielectric spectroscopy results indicate that the dielectric constant and dielectric loss of nanocomposites are positively correlated with the filler's contents. The tested dielectric constant of composites increase from 8.42 (5 wt% fillers content) to 10.1 (20 wt% fillers' content), coupled with an increase on electrical breakdown strength from 21.22 to 31.46 kV/mm. The calculated energy density also increases from 0.016777 to 0.044234 J/cm 3 .